Pengaruh Profitabilitas, Leverage, Komite Audit, dan Karakter Eksekutif Terhadap Tax Avoidance - Pitaloka, Syifa; Aryani Merkusiawati, Ni Ketut Lely (E-Jurnal Akuntansi; Vol 27 No 2 (2019), 2019)
Tax avoidance is an action taken to minimize tax payments legally by utilizing loopholes in tax regulations. This study aims to examine the effect of profitability, leverage, audit committee, and executive character on tax avoidance. Manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017, with a total sample of 68 companies so that the number of observations was 204 selected as samples in this study. The sample selection uses probability sampling with purposive sampling technique. Based on the result of multiple linear regression analysis the results show that profitability, leverage, and executive character have a positive effect on tax avoidance, while the audit committee has a negative effect on tax avoidance. Keywords : Tax avoidance, profitability, leverage, audit committee, character executive